2013
DOI: 10.2478/agri-2013-0002
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Organic Carbon Pool in Agricultural Soils and its Different Development in Individual Agro-Climatic Regions of Slovakia

Abstract: Soil organic carbon (SOC) is one of the basic parameters of soil productivity and quality. Generally soil has potential to sequestrate or release organic carbon depending on land use/management and climatic conditions. The main aim of this article is to show changes in SOC in agricultural land of Slovakia over almost the last 40 years on the basis of modelling data of SOC stock by the RothC model and unequal development of SOC stock on agro-climatic regions of Slovakia. The results received show that average S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Although little is known about homegarden soils specifically, longterm land management strongly affects soil organic carbon (SOC) concentration and stock (Ogle et al, 2005;Branca et al, 2013), as well as its labile and recalcitrant fractions (Yu et al, 2017). Quantitative and qualitative aspects of SOC may be used as indicators of soil quality and sustainable productivity (Lal, 2006), but they are superimposed on effects of precipitation (Jobbagy and Jackson, 2000), moisture (Wiesmeier et al, 2013), elevation (Leifeld et al, 2005;Barančíková et al, 2013), and vegetation (Fu et al, 2010). Studies in Europe and North America revealed that intensive tillage reduces SOC (Kasper et al, 2009;Hontoria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although little is known about homegarden soils specifically, longterm land management strongly affects soil organic carbon (SOC) concentration and stock (Ogle et al, 2005;Branca et al, 2013), as well as its labile and recalcitrant fractions (Yu et al, 2017). Quantitative and qualitative aspects of SOC may be used as indicators of soil quality and sustainable productivity (Lal, 2006), but they are superimposed on effects of precipitation (Jobbagy and Jackson, 2000), moisture (Wiesmeier et al, 2013), elevation (Leifeld et al, 2005;Barančíková et al, 2013), and vegetation (Fu et al, 2010). Studies in Europe and North America revealed that intensive tillage reduces SOC (Kasper et al, 2009;Hontoria et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The initial SOC content was used for running the RothC model to equilibrium (10 000 years) under constant environmental conditions (Coleman and Jenkinson 1996). The empirically derived relationship was set between inert organic matter and the total stock of organic carbon (Falloon et al 2002, Barančíková 2013, Hábová et al 2019. Data of carbon and radiocarbon ages were received in equilibrium mode (initial soil state, initial radiocarbon age) and were applied to run the model in short-term mode , and for prediction in long-term mode (2022-2100).…”
Section: Input Datamentioning
confidence: 99%
“…Data of carbon and radiocarbon ages were received in equilibrium mode (initial soil state, initial radiocarbon age) and were applied to run the model in short-term mode , and for prediction in long-term mode (2022-2100). Literature data for RMSE for long-term field experiments modelling were between 2% and 30% (Smith et al 1997, Falloon and Smith 2002, Guo et al 2007, Barančíková et al 2013, Hábová et al 2019.…”
Section: Input Datamentioning
confidence: 99%
See 2 more Smart Citations